Republic of Yemen Education Status Report : Challenges and Opportunities - World Bank (Washington, DC, 2014)
This report is motivated by two main considerations. First, after three decades of Yemen's impressive continuous expansion of education, the time is ripe to assess the outcomes of its education system and document its strengths and challenges. Second, in the long run, Yemen is poised to be more integrated in the regional and global economy. At this juncture, it is only wise to reflect on whether the recipes that have enabled past successes will be sufficient and relevant to sustain these successes and to build on them to take up looming new challenges. The Government of Yemen requested the World Bank to assist its efforts to forge a holistic approach to developing the education sector. These efforts would include strengthening linkages among the different levels of education, comprehensively addressing systemic issues, and enhancing the efficiency and effectiveness of the system as a whole. This report addresses the first phase of the work. It provides a diagnostic summary of the education system and offers a menu of options to address the issues identified and to advance the system.